Study on Hydrate Phase Equilibrium Diagram of Methane Containing System Based on Thermodynamic Model - Liang, Hao; Duan, Yonggang; Pei, Jun; Wei, Na (Frontiers in Energy Research, 2021)
Natural gas hydrate is a potential energy source in the future, which widely occurs in nature and industrial activities, and its formation and decomposition are identified by phase equilibrium. The calculation of multicomponent gas phase equilibrium is more complex than that of single component gas, which depends on the accurate model characterized by enthalpy and free energy. Based on the Kvamme-Tanaka statistical thermodynamic model, theoretical and experimental methods were used to predict and verify the phase equilibria of pure methane hydrate and car-bon dioxide hydrate in the temperature range of 273.17-289.05 K. The phase equilibria curves of methane-containing gases such as CH4+CO2,CH4+C2H6,CH4+H2S and CH4+CO2+H2S under different mole fractions were drawn and analyzed, and the decomposition or formation enthalpy and free energy of hydrate was calculated. The research results are of great significance to the development and utilization of gas hydrate and the flow safety prediction of gas gathering and transportation.